Protein Bioinformatics: From Protein Modifications and Networks to Proteomics - Wu, Catherine H.; Arighi, Cecilia N.; Ross, Karen E. (Methods in Molecular Biology, 2017)
Protein Bioinformatics Databases and Resources -- UniProt Protein Knowledgebase -- Tutorial on Protein Ontology Resources -- CATH-Gene3D: Generation of the Resource and its Use in Obtaining Structural and Functional Annotations for Protein Sequences -- Structure-Based Virtual Screening -- Bioinformatics Analysis of Protein Phosphorylation in Plant Systems Biology Using P3DB -- Navigating the Glycome Space and Connecting the Glycoproteome -- Impact of Nonsynonymous Single-Nucleotide Variations on Post-Translational Modification Sites in Human Proteins -- Analysis of Cysteine Redox Post-Translational Modifications in Cell Biology and Drug Pharmacology -- Analysis of Protein Phosphorylation and Its Functional Impact on Protein-Protein Interactions via Text Mining of the Scientific Literature -- Functional Interaction Network Construction and Analysis for Disease Discovery -- Prediction of Protein Interactions by Structural Matching: Prediction of PPI Networks and the Effects of Mutations on PPIs that Combines Sequence and Structural Information -- NDEx: A Community Resource for Sharing and Publishing of Biological Networks -- Bioinformatics Analysis of Functional Associations of PTMs -- Bioinformatics Analysis of PTM-Modified Protein Interaction Networks and Complexes -- iPTMnet: Integrative Bioinformatics for Studying PTM Networks -- Protein Identification from Tandem Mass Spectra by Database Searching -- Bioinformatics Analysis of Top-Down Mass Spectrometry Data with ProSight Lite -- Mapping Biological Networks from Quantitative Data-Independent Acquisition Mass Spectrometry Proteomic Data: Data to Knowledge Pipelines -- Annotation of Alternatively Spliced Proteins and Transcripts with Protein-Folding Algorithms and Isoform-Level Functional Networks -- Computational and Statistical Methods for High-Throughput Mass Spectrometry Based PTMs Analysis -- Cross-Species PTM Mapping from Phosphoproteomic Data. .